South Africa’s service delivery in the 4IR era: The need for responsible leadership - Nkosingiphile E. Mkhize; Christian Kayembe; Xolani Thusi (Africa’s Public Service Delivery & Performance Review)
Background: It is argued that fourth industrial revolution (4IR) and its technologies need not just ethical leadership but also a more effective kind of leadership known as responsible leadership to be successfully implemented and adopted. Technology has the potential to enhance significantly existing service delivery mechanisms.